Evaluation of gait characteristics in subjects with locomotive syndrome using wearable gait sensors - Yuki Saito (BMC Musculoskeletal Disorders, 2022)
Abstract Background Individuals with locomotive syndrome (LS) require nursing care services owing to problems with locomotion and the musculoskeletal system. Individuals with LS generally have a reduced walking speed compared with those without LS. However, differences in lower-limb kinematics and gait between individuals with and without LS are not fully understood. This study aimed to clarify the characteristics of the gait kinematics of individuals with LS using wearable sensors. Methods We assessed 125 participants (mean age 73.0 ± 6.7 years) who used a public health promotion facility. Based on the 25-question Geriatric Locomotive Function Scale (GLFS-25), these participants were grouped into the non-LS (GLFS-25 < 7), LS-stage 1 (GLFS-25 7–16), and LS-stage 2 (GLFS-25 ≥ 16) groups (larger GLFS-25 scores indicate worse locomotive ability). Spatiotemporal parameters and lower-limb kinematics during the 10-m walk test were analyzed by the “H-Gait system”, which is a motion analysis system that was developed by the authors and is based on seven inertial sensors. The peak joint angles during the stance and swing phases, as well as the gait speed, cadence, and step length were compared among all groups. Results There were 69 participants in the non-LS group, 33 in the LS-stage 1 group, and 23 in the LS-stage 2 group. Compared with the non-LS group, the LS-stage 2 group showed significantly smaller peak angles of hip extension (9.5 ± 5.3° vs 4.2 ± 8.2°, P = 0.002), hip flexion (34.2 ± 8.8° vs 28.5 ± 9.5°, P = 0.026), and knee flexion (65.2 ± 18.7° vs 50.6 ± 18.5°, P = 0.005). The LS-stage 1 and LS-stage 2 groups had a significantly slower mean gait speed than the non-LS group (non-LS: 1.3 ± 0.2 m/s, LS-stage 1: 1.2 ± 0.2 m/s, LS-stage 2: 1.1 ± 0.2 m/s, P < 0.001). Conclusions The LS-stage 2 group showed significantly different lower-limb kinematics compared with the non-LS group, including smaller peak angles of hip extension, hip flexion, and knee flexion. It would be useful to assess and improve these small peak joint angles during gait for individuals classified as LS-stage 2.